Аналіз розвитку наукових підходів до типології та класифікації натуральних лісових ландшафтів - Мельнійчук, Михайло Михайлович; Чабанчук, Валентина Юріївна; Melniichuk, Mykhailo M.; Chabanchuk, Valentyna Yu. (Дніпропетровський національний університет імені Олеся Гончара, 2016)
Проаналізовано історію розвитку досліджень лісової типології від її зародження до сучасного етапу. Виявлено відмінності між двома основними напрямами у типології лісу: екологічному і ботанічному. Встановлено зв’язки між дослідженнями різних учених у різні історичні періоди, виявлено недоліки та переваги кожного з основних підходів до визначення типу лісу. На основі аналізу праць Г. Ф. Морозова, А. А. Крюденера, Є. В. Алексєєва, П. П. Кожевнікова, Д. В. Воробйова, П. С. Погребняка, А. К. Каяндера, В. М. Сукачова та інших учених зроблено висновок, що лісотипологічна наука зазнала свого розквіту у XIX столітті. На сучасному етапі варто зазначити деякий занепад цього напряму досліджень, оскільки лише деякі науковці продовжують вивчення типів лісу, зокрема, М. М. Вересін, В. І. Білоус, М. А. Голубець та ін., але характер їхніх праць або регіональний або вибірковий (наприклад, М. М. Вересін досліджував лише діброви). Багато праць присвячено антропогенним лісовим ландшафтам, проте саме в умовах антропогенізації актуальності набуває необхідність глибшого вивчення застосування типологічного вчення для раціонального використання лісових ресурсів та збереження осередків натуральних лісових ландшафтів.

This article analyzes the process of formation of modern forest typology in Ukraine. The study deals with the different stages of the research forest typology science from its beginnings to the modern stage. We explored the works of scientists representatives of two main directions in the forests typology, such as botanical and ecological. One of them has developed in the north of Russia, where forest landscapes did not suffer from the human impact. This area of forest typology was developed in the works of A. K Kayander, V. M. Sukachov and his students. Another trend appeared in Ukraine, where forests have undergone human activities. This trend has developed in the works of E. V. Alekseev, P. S. Pogrebnyak, D. V. Vorobov and others. As a result, our research presents links between the works of various scientists, its found differences between the main areas of forest typology, their advantages and disadvantages. In a botanical approach forest type identified with plant association. On the other hand, ecological direction of forest typological classification takes into account environmental conditions. Based on the analysis it should be noted that in the XXI century forest typology science іs declining. Although it has experienced its heyday in the XIX century, when the theoretical foundations of the science were formulated. Since only a few scientists continue to study forest types (for example Veresin M. M., Belous V. I., Holubec M. A. and others), their works are narrowly directed and apply only to a particular forest type (for example oak) or a particular region. At present time many scientists have devoted their research to anthropogenic forest landscapes, including Davydchuk V.S., Denysyk G. I., Molchanova A. A. They continue works of Milkov F. M. and focus their attention on the impact of human and economic activities on the forest landscapes. As a result, it should be noted the necessity of restoring and deeper studying of previous experience of forest typology science and its future development. It is necessary to introduce anthropogenic landscapes to forest typology, although pay more attention to natural forest landscapes for the rational use of forest resources and preserving as much as possible the natural habitat of forests and slowing antropohenization.
Analysis of scientific approaches to the typology and classification of natural forest landscape
Keywords: тип лісу; фітоценологія; лісова типологія; тип насадження; едафічна сітка; forest typology; forest type; planting type; edaphic grid; phytosociology